THE ANTHROPOLOGICAL AND ECOLOGICAL IMPORTANCE OF TIDAL FLATS TO JAPAN AND KOREA WITH SPECIAL REFERENCE TO OYSTER-GATHERING ACTIVITIES - Jun Takeda; Eung-Cheol Lee; Kyoung-Mann Cho (Lowland Technology International, 2001)
Tidal flats of the estuarine ecosystem, reef flats of the coral ecosystems and mangrove ecosystems have up until now ensured the food availability of biologically diverse marine resources on a year-round basis. Traditionally, fishing-gleaning activities have been carried out on a daily basis by women, children and the agedm using non-specialized tecniques or technologies on reef flats in the Ariake Sea, Japan and along the west coast of South Korea. These flats and mangrove ecosystems are covered by the sea twice a day when the tide is at flood, and they are uncovered at ebb. Therefore, it has given people the opportunity to enjoy a supply of oysters and other marine resoources two times a day since ancient times. Oyster-gathering activities through traditional fishing-gleaning strategies on tidal flats in Japan and Korea are, in this study, focused on and discussed in terms of ecological anthropology.